2006
DOI: 10.1369/jhc.6a6999.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Comparison of Quantity, Quality, and Microarray Performance of RNA Extracted From Formalin-fixed, Paraffin-embedded, and Unfixed Frozen Tissue Samples

Abstract: S U M M A R Y Microarrays have been used to simultaneously monitor the expression of thousands of genes from biological samples, an approach that can potentially uncover previously unrecognized functions of genes. Microarray analyses can rarely be conducted retrospectively because of the requirement for RNA to be obtained from fresh or unfixed frozen tissues. Archived pathology specimens would need to be used for retrospective analyses, and these are typically preserved as formalin-fixed, paraffin-embedded (FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 35 publications
5
71
1
Order By: Relevance
“…We demonstrated that FFPE tissue has high sensitivity, specificity and accuracy in comparison with deep-frozen tissue for HPV detection in LSCC. These findings confirm and expand the results of studies of other authors for lung and cervical cancers [16][17][18]. Farragher et al [16] observed a remarkably high level of present cells in both frozen and FFPE samples.…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated that FFPE tissue has high sensitivity, specificity and accuracy in comparison with deep-frozen tissue for HPV detection in LSCC. These findings confirm and expand the results of studies of other authors for lung and cervical cancers [16][17][18]. Farragher et al [16] observed a remarkably high level of present cells in both frozen and FFPE samples.…”
Section: Discussionsupporting
confidence: 89%
“…It is nevertheless desirable to improve the sensitivity of FFPET arrays. Low sensitivity rates of around 50% relative to FT arrays have been reported by others (Bibikova et al, 2004;Scicchitano et al, 2006) and may be due to the presence of residual nonreversed chemical modifications that reduce the efficiency or completely prevent in vitro transcription to cRNA (Godfrey et al, 2000;Bibikova et al, 2004;Lee et al, 2005b). Our archival FFPET RNA samples were similarly (and extensively) degraded, yet cRNA yields varied widely (5 -28 mg).…”
Section: Discussionmentioning
confidence: 60%
“…Whereas RT -PCR interrogation of archival FFPET has proven to be a reliable tool and is widely used (Cronin et al, 2004), this approach is unsuitable for large scale discovery-based investigation owing to the limited number of genes that can be assayed in one experiment. RNA from freshly prepared FFPET may be minimally degraded (von Ahlfen et al, 2007) and their transcript profiles correlate very well with those from paired unfixed FT (Lee et al, 2005a;Scicchitano et al, 2006;Frank et al, 2007), but these samples lack the requisite clinical follow-up data for correlation with expression data.…”
mentioning
confidence: 99%
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…30,83 Despite these concerns, several studies have shown comparable biological information between genome-wide microarray analysis from matched fresh frozen and formalin-fixed paraffin-embedded tissue. 30,32,72,74,75,77,78 The use of formalin-fixed paraffin-embedded rather than fresh frozen tissue clearly allows more practical applications of gene microarray analysis. The National Cancer Institute estimates that 85% of all cancer surgeries are performed in community hospitals, which historically have not had the resources for procuring snap frozen tumor samples.…”
Section: Discussionmentioning
confidence: 99%